Kualitas nonflaky krekers dengan kombinasi tepung tempe kacang gude (Cajanus cajan) dan bawang hitam (Allium sativum) - Febpi Lina Santoso; Yuliana Reni Swasti; Ekawati Purwijantiningsih (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Non-flaky crackers are a snack made from wheat flour, which are not layered, dense, massive, and crunchy. The crackers in this study were made by combining flour, pigeon pea tempeh flour (Cajanus cajan) and black garlic (Allium sativum). The purpose of this study was to determine the quality of the crackers and the best combination of flour, pigeon pea tempeh flour and black garlics. This study used a completely randomized design with three repetitions. The ratio of flour, pigeon pea tempeh flour, and black garlic in the control was 100:0:0; in product A that is 85:10:15; in product B that is 70:20:10; and in product C that is 55:30:5. Crackers of all treatments were analyzed chemically, physically, microorganism, and organoleptic. Crackers with the best combination were product A with a ratio of 85% flour: 10% pigeon pea tempeh flour: and 5% black garlics with a moisture content of 3.36%, ash content of 1.46%, fat content of 20.56%, protein content of 9.35%, carbohydrate content 65.26%, antioxidant activity of 51.25%, total plate number of 1.7 x 102, total yeast and mould of 7.6 x 101, texture of 10.64 N and organoleptic score of 3.13.